Cardiorespiratory fitness and quality of life at different exercise intensities after myocardial infarction Aptitud cardiorrespiratoria y calidad de vida postinfarto en diferentes intensidades de ejercicio - De Araujo C.L.P.* (2010)
Background: Studies relating physical exercises and health have contributed to elucidate the influence of sedentary habits on the incidence of cardiovascular diseases. Objective: To compare the effect of different intensities of aerobic exercises on patients' functional capacity (VO 2peak) and quality of life after acute myocardial infarction. Methods: Eighty-seven men (57.7 ± 6.1 years old) were enrolled in this prospective study and assigned to one of three groups: a) high-intensity physical training (n=29) at 85% maximum heart rate for 12 weeks; b) moderate-intensity training (n=29) at 75% maximum heart rate for 12 weeks; and c) control group (n=29), who were followed. The training groups did aerobic exercises five times a week in 45-minute sessions, besides muscular strengthening and stretching exercises. Maximum VO2 was measured through a cardiopulmonary test, and quality of life was assessed through the MacNew Questionnaire. Results: Two-way ANOVA revealed a significant increase in VO 2peak (p<0.05) in the high-intensity training group (from 29.9 ± 2.2 ml/kg.min to 41.6± 3.9 ml/kg.min) compared with the moderate-intensity training group (from 32.0 ± 5.3 ml/kg.min to 37.1 ± 3.9 ml/kg.min). Additionally, both training groups showed a significant increase in this parameter compared with the control group (from 31.6 ± 3.9 ml/kg.min to 29.2 ±4.1 ml/kg.min). Quality of life improved significantly (p<0.05) in the high-intensity training group (from 5.66 to 6.80) and in the moderate-intensity training group (from 5.38 to 6.72), but not in the control group (from 5.30 to 5.15). Conclusion: Exercises of greater intensity resulted in an increase in functional capacity and quality of life in patients after myocardial infarction.